POTENSI NIOSOMAL GEL SEBAGAI PENGHANTARAN OBAT ANTIINFLAMASI MELALUI SISTEM PENGHANTARAN TRANSDERMAL - Nursal, Fith Khaira; Nining, Nining (Universitas Imelda Medan, 2024)
Nonsteroidal anti-inflammatory drugs (NSAIDs) are one of the most popular drugs used, and the WHO model lists essential medicines due to their efficacy in reducing pain and inflammation. Orally administered is prone to causing adverse reactions, while injections administered are not conducive to self-administration of the drug because the patient feels uncomfortable, thereby reducing patient compliance. Transdermal delivery is one solution because it has the potential to improve the safety profile and increase the drug's bioavailability. The use of drug delivery systems based on colloidal particulate carriers such as niosomes has advantages over conventional dosage forms because these particles can act as a reservoir containing the drug and can increase penetration. Based on the discussion presented, gel-based niosomes formulations in various research results show better drug release and permeation through the skin compared to conventional formulations. The presence of cholesterol and surfactant components plays an important role in helping drug permeation through the skin in terms of increasing the number of permeating drug molecules and the depth of permeation that occurs. Hydrogel-forming polymers are the first choice for loading niosomes because they are biocompatible and easy to obtain. Carpobol is the polymer most chosen because of its ability to spread easily, forming homogeneous and transparent preparations.